Kopontren dan Ekosistem Halal Value Chain - Arna Asna Annisa (Jurnal Ilmiah Ekonomi Islam, 2019)
The development of the economic potential of Islamic boarding schools can have a positive impact on improving the national economy. As an educational institution, Islamic boarding schools have the potential of human resources which are also large for high fighting ability, which supports accompanied by capabilities that become a great potential that can become the basis of Indonesia's new economic flows through strengthening boarding schools (kopontren). This paper aims to examine the ecosystems in Islamic boarding schools which have to do with changes in the lifestyle of its members to apply halal values. The research using this qualitative descriptive method. Based on the results of the analysis, the role of kopontren as the driving force of the boarding school is an important diversion as a determinant of how to turn on the halal value chain in every part of the environment in the Islamic boarding school ecosystem with halal values in production, distribution for consumption needs goods or services.